Environmental Education to Preserve the Environment in Current Legislation in Angola - Fazenda, Augusto José (Archives of Business Research, 2023)
In Angola, the environmental problem is manifested as an explicit concern, so that, in the Basic Law of the Environment, it is directed that all citizens have the right and the duty to receive environmental education for better understand the phenomena of environmental balance, an essential basis for conscious action in defense of the National Environmental Policy. The present study aims to identify the existing guidelines in the legislation in force in Angola for environmental education and the preservation of the environment, as well as the contradictions that occur in local community participation, in this context. In the investigation, the review of laws and decrees, interviews with local rulers and participant observation were used as methods. The study allowed us to conclude that in the legislation in force in Angola there are sufficient guidelines for environmental education and the preservation of the environment, but for the creation of a healthy environment there are weaknesses in local community participation, mainly due to the negligence of some of the local governments that aggravate the situation, due to the non-compliance with the norms for the preservation of the environment and the inadequacies in the incorporation of environmental education in the educational process that guarantees the local community participation in the defense of the national environmental policy.